Greenland, Kejser Franz Josef Fjord, Northeast Greenland National Park - Boyd, Louise Arner, 1887-1972 (1931)
Fig. 183 - Looking north across Franz Josef Fiord from Kjerulf Fiord. On the left is Gregory Valley. July 31, 1931. (Caption from Boyd, L. A. (1935). The Fiord Region of East Greenland (pp. 128). New York: American Geographical Society.) Looking north across Franz Josef Fiord from Kjerulf Fiord. On the left is Gregory Valley. July 31, 1931. From: The Fiord Region of EAst Greenland. Fig. 183. Boyd, Louise A. (1935). The Fiord Region of East Greenland. New York: American Geographical Society